Comparison of Rice N Uptake in Paddies with Different Organic Carbon - VASEGHI*, S.; VALYNEJAD†, M.; FALLAH‡, V.M.; PAZIRA†, E.; FALLAH‡, A.; MOAMENI‡, A. (Asian Journal of Chemistry, 2024)
Efficient use of all inputs is vital to achieve and sustain high crop yields, maintain resource quality and minimize environmental pollution. Fertilizer N is one of the major inputs in rice production. Blanket fertilizer recommendations do not take into account the high field-to-field variability and within-season dynamic changes in indigenous N supply. Since the plant growth reflects the total N supply from all sources, plant N status will be a good indicator of N availability to crops at any given time. Leaf colour chart (LCC) is simple portable diagnostic tool, to determine the timing of N top dressing. We used it to test need-based N-management approaches for rice (Oryza sativa L.) and compared LCC with split three rates (45, 90 and 135) and three timing at two sites, in northern Iran. Grain yield, yield attributes, total N uptake and fertilizer-N use efficiency were measured. All treatments showed significant grain yield increase relative to zero-N control. Yield loss was observed when split 135 timing was used in both sites due to lodging and pest damage. Grain yield of LCC treatments were higher than split treatments. The grain yield of zero-N control in site 2 was 18.5 % higher than that of site 1 due to higher soil organic matter percent. LCC 5 treatment had higher AE than LCC 4 and fixed - 135 at the less N rate. As a result LCC treatments indicated that N management based on LCC shade 5 helped avoid over application of N to rice.